A reply to Listo, Saberian and Thivierge (2023) - Ralph De Haas; Alexander Popov (Institute for Replication (I4R), 2023)
Listo, Saberian and Thivierge (2023) conduct a careful replication of De Haas and Popov (2023) using the data, code, and instructions we made available at the time of publication. They highlight an inconsistency between the table notes and the main text in how the clustering of standard errors is described; uncover a coding mistake in the GMM regressions; and show that weak instruments are unlikely to bias our 2SLS coefficients. In this reply, we show that our results remain economically meaningful and statistically precise (though smaller in magnitude) when we (i) cluster standard errors by country in the country panel; (ii) correct the GMM code; and (iii) include or exclude China in the country and industry samples.
Keywords: 330